Exploring critical factors for choice of mobile service providers and its effectiveness on Malaysian consumers - Haque, A. K. M. Ahasanul; Ahmed, Ismail Sayeed; Rahman, Sabbir (2010)
From the late 1990 to till now the growth rate of Malaysian telecommunication sector is remarkable manner. Under this circumstances new players to these businesses soaring dramatic business competition. Nowadays they are trying to attract customers by offering aggressive marketing strategy for instance: price promotion. As competition is looming among the companies, it deems a necessity for them to learn the consumers’ inherent perceptions that can play significant factors in terms of choosing the tele-service providers. The aim of this study was to find out what were the factors that may have played significant role to select the telecommunication service providers. To accomplish the objectives, this research explains the related concepts and theories; revealed and synchronized literature on consumer perception. In general this research has an intention to develop a research framework grounded on a strong theoretical and literature review background. The survey instruments employed on Malaysian consumers included demographic background, price, service quality, product quality and availability, and promotional offers for consumer perception. Thus the structural equation modeling approach was necessary in order to examine the variables. The data analysis was conducted using SPSS and AMOS (Analysis of Moment Structure) with the software package for windows. From the result it is revealed that paths are related to the casual processes significantly. Among all the significant variables, from our result, Price is the most important among our respondents followed by Service quality, product quality and promotion. However, the findings of this study may provide needed feedback and contribute to the improvement of players’ strategy and their marketing program.